A Visual Survey of Global Slab Geometries With ShowEarthModel and Implications for a Three‐Dimensional Subduction Paradigm. Issue 6 (29th June 2018) - Jadamec, Margarete A.; Kreylos, Oliver; Chang, Benjamin; Fischer, Karen M.; Yikilmaz, M. Burak
Abstract : Increasing volumes of digital data, combined with advances in visualization, allow for a new three‐dimensional (3D) conceptualization of modern subduction systems. Here we present 16 visual exploration sessions with the ShowEarthModel program that interrogate modern slab morphologies on Earth. These virtual voyages through the Earth's interior provide a snapshot into the four‐dimensional evolution of plate tectonics, captured by the modern state of slab structure. Examining the modern subduction system in an interactive 3‐D framework provides an improved conceptualization of the morphology of slabs. The movies demonstrate that unlike the modern mid‐ocean ridge system, modern subduction systems are laterally discontinuous features, making lateral slab edges prevalent. The 3‐D visualizations elucidate the manner in which slabs intersect and overlap, processes that occur in at least six of the Earth's major subduction zones. The observed variability within a given subduction zone as well as the physical presence of intersecting slabs suggests that slab gaps and slab windows are common. The 3‐D rendering shows relative differences in the radius of curvature for arcuate slabs, as well as the variability in dip within a given subduction zone. Addressing the complex geometries of subducted lithosphere in this way can place constraints on outstanding questions of subduction dynamics including slab strength, mantle rheology, mantle flow circulation, and plate‐asthenosphere coupling. By conceptualizing the modern subduction system on Earth in 3‐D space, this paper contributes to the paradigm shift from a two‐dimensional (2‐D) to 3‐D framework for interpreting the subduction process. Plain Language Summary: Seismic data characterizing the modern plate tectonic boundaries on Earth show that the subducted lithosphere varies significantly both between and within subduction zones, suggesting that a 2‐D paradigm is no longer adequate to describe the subduction process. Increasing volumes of digital data, combined with advances in visualization, now allow for a new 3‐D conceptualization of modern subduction systems. Here we present the open‐source ShowEarthModel software and 16 movies that provide a snapshot into the four‐dimensional evolution of plate tectonics on Earth, by showing a series of virtual voyages through the Earth's interior. Examining the modern subduction systems in an interactive 3‐D framework provides a new conceptualization of the 3‐D morphology of subducted lithosphere. Visualizing the 3‐D connectivity demonstrates how subducted plates overlap in 3‐D space, addressing the question of what actually defines the lateral limits of a subduction zone and how one distinguishes one subduction zone from the next. Six inherently 3‐D aspects of slab geometries are identified, and the implications on fluid‐like flow in the Earth are discussed. This raises questions, as well as places constraints on, first‐order properties of subduction dynamics including the nature of subduction zones, slab strength, mantle rheology, mantle flow rates, and plate‐asthenosphere coupling. Key Points: This paper presents conceptualizations of the modern subduction system on Earth in 3‐D space Six inherently 3‐D aspects of slab geometry are placed in the context of mantle flow in subduction zones The ShowEarthModel program allows for intuitive exploration of point cloud data facilitating new paradigms